2013
DOI: 10.1021/jo401759z
|View full text |Cite
|
Sign up to set email alerts
|

Ascertaining the Suitability of Aryl Sulfonyl Fluorides for [18F]Radiochemistry Applications: A Systematic Investigation using Microfluidics

Abstract: Optimization of [(18)F]radiolabeling conditions and subsequent stability analysis in mobile phase, PBS buffer, and rat serum of 12 aryl sulfonyl chloride precursors with various substituents (electron-withdrawing groups, electron-donating groups, increased steric bulk, heterocyclic) were performed using an Advion NanoTek Microfluidic Synthesis System. A comparison of radiochemical yields and reaction times for a microfluidics device versus a conventional reaction vessel is reported. [(18)F]Radiolabeling of sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
104
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(113 citation statements)
references
References 38 publications
7
104
1
1
Order By: Relevance
“…In both examples, we obtained maximum isolated yields of >80%. The case of 9-Cl was particularly noteworthy since radiolabeling conducted using anhydrous conditions demonstrated that the fluorination reaction can occur only at low temperatures and with a higher concentration of precursor (>2 mg/mL), probably due to competing decomposition of the acid [16]. Instead, in the presence of the hydrous complex (5% H 2 O), a low concentration (0.5 mg/mL) of 9-Cl was sufficient to obtain 91% radiochemical incorporation yield at 30°C at a flow rate of 20 μL/min for both precursor and fluorination complex.…”
Section: Discussion Of Results On Model Structures the Results Repormentioning
confidence: 99%
“…In both examples, we obtained maximum isolated yields of >80%. The case of 9-Cl was particularly noteworthy since radiolabeling conducted using anhydrous conditions demonstrated that the fluorination reaction can occur only at low temperatures and with a higher concentration of precursor (>2 mg/mL), probably due to competing decomposition of the acid [16]. Instead, in the presence of the hydrous complex (5% H 2 O), a low concentration (0.5 mg/mL) of 9-Cl was sufficient to obtain 91% radiochemical incorporation yield at 30°C at a flow rate of 20 μL/min for both precursor and fluorination complex.…”
Section: Discussion Of Results On Model Structures the Results Repormentioning
confidence: 99%
“…1 This procedure requires positron-emitting biomolecules that selectively bind to the biological area of interest (i.e., cellular targets or receptors). The radioisotope 18 F is often considered to be the best positron-emitter, owing to its appropriate decay half-life (109.7 min), which balances patient dose with pharmacokinetic clearance of the tracer itself. The half-life is also long enough to allow time for synthesis of radiotracers without much decay loss, and hence, 18 F can be manufactured commercially at offsite locations then shipped to PET centers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Generally, the synthesis involves several procedural steps. The first step is the generation of the radioisotope [ 18 F]fluoride, which is produced by the proton bombardment of the target material (heavy oxygen water or H 2 18 O)), and the radionuclide is released from the cyclotron in the form of [ 18 2), or a large organic counterion, e.g. tetrabutyl ammonium bicarbonate.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations